2020
DOI: 10.5435/jaaos-d-19-00722
|View full text |Cite
|
Sign up to set email alerts
|

Managing Lymphedema in Fracture Care: Current Concepts and Treatment Principles

Abstract: Lymphatic flow plays a notable role in the regulation of bone formation and remodeling. Chronic accumulation of the lymph fluid within tissues may lead to issues with proper bone healing after fractures, emphasizing the importance of proper management of lymphedema after trauma. Many associated risk factors place patients at risk for lymphedema, including previous surgery with nodal dissection, radiation therapy, infection, malignancy, family history of congenital lymphedema, and trauma. The benchmark imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In addition, prompt treatment of pain, widely-regarded as the fifth vital sign, is beneficial for reducing suffering, readmissions and emergency department visits after hospital discharge [ 36 ]. Although many studies have reported on how to eliminate chronic post-traumatic lymphedema [ [37] , [38] , [39] ], the effect of lymphatic drainage on acute post-traumatic hematoma and pain is not clear. With the treatment of anti-PDPN neutralizing antibody, we determined that improving lymphatic drainage reduces acute post-traumatic edema and pain, suggesting that defects in lymphatic drainage plays a key role in the early complications of traumatic fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prompt treatment of pain, widely-regarded as the fifth vital sign, is beneficial for reducing suffering, readmissions and emergency department visits after hospital discharge [ 36 ]. Although many studies have reported on how to eliminate chronic post-traumatic lymphedema [ [37] , [38] , [39] ], the effect of lymphatic drainage on acute post-traumatic hematoma and pain is not clear. With the treatment of anti-PDPN neutralizing antibody, we determined that improving lymphatic drainage reduces acute post-traumatic edema and pain, suggesting that defects in lymphatic drainage plays a key role in the early complications of traumatic fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to bone and soft tissues are usually followed by edema, which develops immediately after soft tissue injury or fracture [6] . Unlike edema from chronic venous obstruction, post-traumatic edema presents with pain at the site of injury, erythema, and increased skin temperature.…”
Section: Lymphatic Response To Traumatic Injurymentioning
confidence: 99%
“…Unlike edema from chronic venous obstruction, post-traumatic edema presents with pain at the site of injury, erythema, and increased skin temperature. These clinical findings are indicative of a protracted inflammatory reaction characterized by immune cell infiltration and activation of an inflammatory cascade [6,7] .…”
Section: Lymphatic Response To Traumatic Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomically, most peripheral superficial lymphatic vessels of the lower leg run along the way of the medial face of the limb, parallel to the superficial great saphenous vein [21] damage, chronic inflammation, and trauma to this specific anatomic area contribute to the development of secondary lower limb lymphedema [22][23][24][25][26]. This site was exactly the spider bite site, where local loxoscelism was developed, where the skin and soft tissue destruction happened to be; the epicenter of the chronic inflammatory process caused by the wound, and where recurrent lymphangitis originated.…”
Section: Fig 3 Wound Detail Note the Broad Rings Of Fibrous And Devit...mentioning
confidence: 99%